ANALISIS PENGGUNAAN MEDIA SOSIAL DIKALANGAN SISIWA KELAS TINGGI SDIT AL-MANAR PEKANBARU - Annisa Ardelia; Guslinda; Dede Permana (STKIP Subang, 2025)
This study aims to describe the motives and patterns of social media use by upper- grade elementary school students. The research uses a descriptive quantitative method with descriptive statistical analysis techniques. The sample in this study consisted of 72 students from grades IV, V, VI at Al-Manar Integrated Islamic Elementary School, Pekanbaru City. The data collection technique and research instrument used in this study were questionnaires, and the data were analyzed using percentage formulas. The research results indicate that the main motives for students' use of social media are for enjoyment (80%), followed by obtaining information (79%), as well as social interaction and relaxation (both 77%). Usage patterns show that the majority of students access social media more than five times a day, with an average duration of one hour, predominantly for consuming entertainment content (82%). The use of social media by students is influenced by conditions such as parental permission and school holidays. The most frequently used application is YouTube (72%), followed by WhatsApp and TikTok (63% each)